Calcium Biofortification of Crops–Challenges and Projected Benefits - Knez, Marija; Stangoulis, James C. R. (Frontiers in Plant Science, 2021)
Despite Ca being an essential nutrient for humans, deficiency of Ca is becoming an ensuing public health problem worldwide. Breeding staple crops with higher Ca concentrations is a sustainable long-term strategy for alleviating Ca deficiency and particular criteria for a successful breeding initiative needs to be in place. This paper discusses current challenges and projected benefits of Ca biofortified crops. The most important features of Ca nutrition in plants are presented along with explicit recommendations for additional exploration of this important issue. In order for Ca biofortified crops to be successfully developed, tested and effectively implemented in most vulnerable populations’ further research is required.